2019
DOI: 10.1155/2019/3616852
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Signatures of Computed Tomography Imaging for Predicting Risk Categorization and Clinical Stage of Thymomas

Abstract: Purpose. The aim of this study is to develop and compare performance of radiomics signatures using texture features extracted from noncontrast enhanced CT (NECT) and contrast enhanced CT (CECT) images for preoperative predicting risk categorization and clinical stage of thymomas. Materials and Methods. Between January 2010 and October 2018, 199 patients with surgical resection and histopathologically confirmed thymoma were enrolled in this retrospective study. We extracted 841 radiomics features separately fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…Yasaka K et al also found that the meanValue was a significant parameter for differentiating HTET from LTET with AUC of 0.89 [18]. Sphericity is the shape feature of the tumor and has been proven as the most significant factor for discriminating histologic subtypes in TET patients [29]. Busyness is a parameter of NGLDM, Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Yasaka K et al also found that the meanValue was a significant parameter for differentiating HTET from LTET with AUC of 0.89 [18]. Sphericity is the shape feature of the tumor and has been proven as the most significant factor for discriminating histologic subtypes in TET patients [29]. Busyness is a parameter of NGLDM, Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Only few scholars have conducted relevant research in the radiomics field. Wang et al [ 26 ] obtained the results that the AUCs were 0.829 and 0.860 for the radiomics signature based on unenhanced and enhanced CT images in differentiating advanced stage thymomas from early stage thymomas, respectively. However, Sui et al [ 27 ] believed that the unenhanced phase could better distinguish high-risk and low-risk thymomas than the enhanced phase, because more texture features were selected from the unenhanced phase than from the enhanced phase, and tumour heterogeneity was better detected in the unenhanced phase, the above studies were similar to our results that the enhanced CT and unenhanced CT radiomics can better differentiating the different stages of thymoma, the enrolled thymomas were confirmed by Masaoka clinical stage and WHO histologic classification.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the texture features extracted in this study were only based on enhanced CT images, but not the plain CT. However, previous study showed that there was no significant difference between radiomics features based on plain CT images and ones based on enhanced CT images for predicting risk categorization of TETs [30]. Third, the tumor, node, metastasis (TNM) [39] or Masaoka [40] staging systems for TETs were not used in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Yasaka K et al also found that the meanValue was a significant parameter for differentiating between HTET and LTET with AUC of 0.89 [21]. Sphericity is the shape features of tumors, and has been proven as the most significant affecting factor for discriminating histologic subtype in TET patients [30]. Busyness is a parameter of NGLDM, which measures the spatial frequency of changes in intensity between nearby voxels of different grey-levels.…”
Section: Discussionmentioning
confidence: 99%